2018
DOI: 10.1177/2050640617751254
|View full text |Cite
|
Sign up to set email alerts
|

Social group disparities in the incidence and prognosis of oesophageal cancer

Abstract: There are substantial disparities in the incidence and prognosis of oesophageal cancer across social population groups, including sex, race/ethnicity, geographical location and socio-economic status. Both squamous cell carcinoma and adenocarcinoma of the oesophagus are more common in men than in women, but the male predominance in adenocarcinoma is stronger and less well understood. The varying incidence and prognosis of oesophageal cancer across racial/ethnic groups show distinct patterns by histological type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
(124 reference statements)
1
22
1
Order By: Relevance
“…However, advancing age and socioeconomic deprivation was impaired to poorer OS in this study. A worse prognosis has been associated with black individuals with esophageal cancer, but this has not held true when adjusting for socioeconomic status, while blacks, Asians, and Hispanics have been shown to undergo lower rates of surgery, when compared to whites, in localized esophageal cancer[ 33 ]. In addition, there were more patients from the geographic Southern region who did not receive any palliative therapy (30.9%) compared to those who received palliative therapy (23.6%, P = 0.003), and notably being from the South was significantly associated with a worse OS on both univariate and multivariable analyses (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, advancing age and socioeconomic deprivation was impaired to poorer OS in this study. A worse prognosis has been associated with black individuals with esophageal cancer, but this has not held true when adjusting for socioeconomic status, while blacks, Asians, and Hispanics have been shown to undergo lower rates of surgery, when compared to whites, in localized esophageal cancer[ 33 ]. In addition, there were more patients from the geographic Southern region who did not receive any palliative therapy (30.9%) compared to those who received palliative therapy (23.6%, P = 0.003), and notably being from the South was significantly associated with a worse OS on both univariate and multivariable analyses (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…More and more research is being directed at developing better treatment and improving prognosis for patients diagnosed with ESCC. Previous studies suggested that certain factors had an effect on the prognosis of ESCC patients however, the systematic analysis of these factors as a prognostic took has not been done [19][20][21][22][23][24]. In the present study, we have analyzed the ESCC patients' data from two academic institutes, SYSUCC and HNCH.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, the majority of the patients were at advanced stages of cancer. Dysphagia and late presentations became the cardinal presentations of EC patients in Ethiopia (23,28,29), Africa (16,33,35,(40)(41)(42) and elsewhere (43)(44)(45)(46). The reason could be because of the fact that esophagus has a remarkable capability to stretch until signi cantly blocked by the tumor (47).In addition, presenting at a late stage of cancer with dysphagia could be linked to failure to understand the early symptoms associated with esophageal carcinoma.…”
Section: Discussionmentioning
confidence: 99%